Caregiving at home (Alzheimer's Association, 1990)
An Alzheimer's Association handbook for Alzheimer's Disease Caregivers.
Keywords: geriatrie; Home Health Nursing; domácí ošetřovatelství; Alzheimerova nemoc; ošetřovatelství; senioři; Geriatric Nursing; Aged; Alzheimer Disease; geriatrické ošetřovatelství; neurologie